Wittgenstein on British Anti-Nazi Propaganda: A Fragment - Venturinha, Nuno; Smith, Jonathan (Nordic Wittgenstein Review, 2018)
This paper contains a historical introduction and an edition of a hitherto unpublished manuscript of Wittgenstein's that was found among G. H. von Wright's materials kept in Helsinki. The document concentrates on British anti-Nazi propaganda and was written in 1945. Wittgenstein's criticism of this kind of propaganda, such as that promoted by Robert Vansittart, is also present in other sources of this period belonging to both the Nachlass and the correspondence.